(untitled) (e-Journal of Linguistics, 2026)
This study examines the transformation of cockfighting, locally known as pei’u manu, within the Sabu Raijua community of East Nusa Tenggara, Indonesia. Traditionally, the practice functioned as a sacred ritual aimed at preventing intergroup violence and restoring communal harmony. Over time, however, its meaning and function have shifted under the influence of modernity, economic pressures, and changing social values. This study employs a qualitative ethnographic approach, utilizing participant observation, in-depth interviews, and document analysis. Data were analyzed thematically to identify shifts in cultural meanings associated with the practice. The findings reveal a significant shift from a communal, sacred ritual centered on peace, morality, and cultural identity to a practice increasingly associated with entertainment, gambling, and economic interests. This study contributes to broader discussions on cultural transformation by demonstrating how local traditions are reinterpreted under contemporary socio-economic conditions, often leading to the reconfiguration of their original meanings.